Analysis of plasma plume parameters in physio-chemical processes of RF plasma jet plume direct in water for the inactivation of Enterococcus bacteria - N. Morshedian; A. Mehramiz; M. Bakhshzadmahmoudi; M. Kharaghani; B. Mohammadhosseini; R. Badrli (AIP Advances, 2023)
The contamination of Enterococcus bacterium is widely observed in the living environment and water. The decontamination of drinking water from the bacterial pollution is an important issue in water treatment. Here, the inactivation of Enterococcus bacteria is studied by placing the dielectric barrier discharge structure, with the RF discharge frequency of 13.56 MHz atmospheric pressure argon plasma jet, directly in water, whereas the water around the plasma plume was seething and the bubbles produced stirring all liquid volume. The ability to place a plasma jet nozzle directly in water for 10 min while maintaining a steady and uniform plasma plume, besides water temperature, provides the effectiveness enhancement in the inactivation of bacteria. The absorption of UV radiation in water is effective, and the role of UV radiation of plasma plume was mainly responsible for the destruction of peptidoglycan, which is the outer layer of Enterococcus. Then, the presence of electrons and plasma plume in water leads to the formation of hydroxyl, hydrogen peroxide, and other reactive radicals that are involved in chemical reactions, which lead to the inactivation of micro-organisms. The number of bacteria decreases from the initial value of 16 × 105 MPN/100 ml to less than 1.2 MPN/100 ml. The spectra of the plasma radiation, with the plume length 2 cm within the water, have been analyzed via the first nitrogen negative system N2+B−X. The plume temperature was calculated to be about 64 °C, which has a good agreement with water temperature measured by using a thermometer at about 67 °C after 15 min at maximum 200 W input power of the plasma jet.